A Preliminary Approach of the Underlying Structure of Swimmers’ Self-Talk in Competition - Kagiorgi Ειρήνη; Zourbanos Νίκος; Stavrou Βασίλης; Hatzigeorgiadis Αντώνης (Inquiries in Physical Education and Sport, 2008)
The aim of the present study was to examine the underlying structure of swimmers’ self-talk during competition. Participants were 174 swimmers, who completed the Automatic Self-Talk Questionnaire for Sports (Ζourbanos et al., in press). The questionnaire assesses four dimensions of positive thoughts (psychup, self-confidence, instruction, and anxiety control) and four dimensions of negative thoughts (worry, somatic fatigue, disengagement, and irrelevant thoughts). Generally, the results showed that swimmers reported more positive and less negative self-talk during competition. Furthermore, no differences were revealed for competitive level, whereas significant differences were revealed for gender, with females scoring higher than males in worry (p< .05). Research on the content and the frequency of swimmers’ self-talk can improve our understanding regarding the role of self-talk in relation to performance and the development of plans to shape athletes’ self-talk during competition.